Effect of superiors' emotional intelligence on subordinates' conflict management styles. - Ho, Soon Wing. (2008)
This study tested the effect of superiors’ emotional intelligence (EQ) (high EQ vs low EQ) on subordinates’ conflict management styles. The implication of this study is to motivate superiors to improve on their EQ, and to encourage organizations to include EQ assessment in the recruitment of managers.